2020
DOI: 10.2147/ndt.s242153
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Attention Deficit Hyperactivity Disorder and Risk of Burn Injury: A Propensity-Matched Cohort Study</p>

Abstract: Purpose: Literature suggests that attention deficit hyperactivity disorder (ADHD) is associated with a high risk of unintentional injury. However, few studies have focused on whether risk of burn injury is relatively high among patients with ADHD. The aim of this study was to investigate whether ADHD affects the risk of burn injury. Materials and Methods: Individuals aged <18 years with a current diagnosis of ADHD (N = 52,705) and age-, sex-, and other comorbidity-matched controls were selected from Taiwan's N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For youths between six and seventeen years old, the increase in risk was about 70 percent. There were no significant differences between boys and girls (Yeh et al, 2020).…”
Section: Accidental Injuriesmentioning
confidence: 66%
“…For youths between six and seventeen years old, the increase in risk was about 70 percent. There were no significant differences between boys and girls (Yeh et al, 2020).…”
Section: Accidental Injuriesmentioning
confidence: 66%
“…Symptoms of ADHD can cause a wide range of functional impairment in daily life, including executive function impairment (Holst and Thorell, 2019 ). It is demonstrated that people with ADHD are prone to injuries and accidents, such as burns (Yeh et al ., 2020 ), fractures (Mangus et al ., 2004 ), concussions (Nelson et al ., 2016 ) and traumatic brain injuries (Rowe et al ., 2004 ; Liao et al ., 2018 ). A few studies have revealed the association between ADHD and traffic accidents (Jerome et al ., 2006 ; Barkley and Cox, 2007 ; Vaa, 2014 ).…”
Section: Introductionmentioning
confidence: 99%